Tipo de Clima Anual para Campina Grande e Areia: Variabilidade e Tipologia - Lima, Paulo Ricardo Cavalcante de (2019)
Understanding the climate of a region is essential to support decision-making processes by public management and provide tools for regional development and economic activities linked to the field, such as agriculture and family farming, important factors that make possible, with some success, survival in the driest region of the country: the Semiarid. The Brazilian Semiarid has remarkable climatic characteristics and presents a great variability both temporal and spatial, mainly due to its extension that covers ten Brazilian states. The static characteristic of classical climate classification methods is sharply criticized for the broader, more general, and less detailed results. However, the latest methods that promote more dynamic climatology are subject to a lack of accessible, concise data on extended series and, at most, daily scales. Given the above, the main objective of this work was to analyze, from 1994 to 2018, for the municipalities of Areia and Campina Grande, both located in the state of Paraíba, the Annual Climate Type (ACT), which is an application of a technique that uses classical methods of climatological classification, however, in a slightly more dynamic way to understand climate characteristics on an annual scale. In addition, the interannual variability of the precipitation and temperature variables for the 25 years of the series and for the Climatological Normal from 1981 to 2010 was analyzed. Moreover, the criteria for the insertion of municipalities in the new delimitation of the semiarid related to the amount of precipitation and aridity index. The basis of Climate Classification Systems used was those of Köppen-Geiger and Thornthwaite. The results showed that, despite the proximity between them, the municipalities of Areia and Campina Grande have very different rainfall, but their distributions have similar behavior. The city of Areia has an average annual rainfall of 1317.6 mm, which makes it 70% wetter than Campina Grande (774.0 mm), but with similar temperature ranges and averages of 22.5 ° C and 23.5 °. C, respectively. The ACT for Areia presents more climate variations than for Campina Grande, this for the two types of Climate Classifications used, and do not necessarily correspond to the usual climate for cities, being more visible in the Thornthwaite method. Thornthwaite's usual climate type for Areia is B1rB'4b’4 and for Campina Grande, C1dA'a ', being for Köppen As' for both locations. Finally, the analysis of the insertion criteria in the delimitation showed that Campina Grande is able to compose the semiarid, unlike Areia. There is still a reflection on the aridity index used for the classification.